Talent Research in Sport 1990–2018: A Scoping Review - Baker, Joseph; Wilson, Stuart; Johnston, Kathryn; Dehghansai, Nima; Koenigsberg, Aaron; de Vegt, Steven; Wattie, Nick (Frontiers in Psychology, 2020)
Several recent systematic and targeted reviews have highlighted limitations in our understanding of talent in sport. A comprehensive profile of where the scientific research has focused would help identify gaps in current knowledge. In this study, we used the PRISMA guidelines for systematic reviews to conduct a search of three databases for talent related research from 1990 to 2018. Peer reviewed articles written in English that met several inclusion criteria were analyzed. A total of 1899 articles were identified and the descriptive findings revealed a relatively narrow focus of research on talent in sport. Specifically, the majority of examined articles focused on a) males only, b) the sport of soccer, c) perceptual cognitive variables, d) developing athletes, e) adult samples, and f) cross-sectional designs. For better or worse, the concept of talent remains a central element of how coaches, practitioners, and scientists think about athlete development. Findings from this study highlight the continued need to explore issues related to talent identification, selection, and development in more diverse samples (e.g., female athletes and younger ages) and contexts (e.g.., from Africa, Asia and South America). There is also a clear necessity to focus on under-researched areas using alternative methodologies.